1993
DOI: 10.1038/eye.1993.12
|View full text |Cite
|
Sign up to set email alerts
|

Corneal epithelial cell migration in humans: ‘Hurricane and blizzard keratopathy’

Abstract: SUMMARYpattern is almost always clockwise. We believe that this specific pattern is likely to be due to the effect of the elec tromagnetic fields of the eye on the migrating epithelial cells and present a theory to explain this phenomenon. In 3 eyes of 2 other patients with chronic epitheliopathies we observed a random distribution of cells that did not con form to any specific pattern. We have termed this con dition 'blizzard keratopathy'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
0
31
1
Order By: Relevance
“…The resulting whorled pattern of corneal abnormality in heterozygous females is presumably a consequence of heterogeneity of expression in limbal stem cell clones (functional mosaicism for ␣-galactosidase expression), similar to the phenomenon described in this study. In reported cases of vortex keratopathy, the whorls always turn clockwise, and it has been suggested that this finding is in response to electrical fields across the corneal surface (Dua et al, 1993(Dua et al, , 1996. In contrast, in our model, both clockwise and counterclockwise whorls were observed, apparently randomly with respect to left and right eyes, but only in the very centre of the cornea.…”
Section: Discussioncontrasting
confidence: 60%
“…The resulting whorled pattern of corneal abnormality in heterozygous females is presumably a consequence of heterogeneity of expression in limbal stem cell clones (functional mosaicism for ␣-galactosidase expression), similar to the phenomenon described in this study. In reported cases of vortex keratopathy, the whorls always turn clockwise, and it has been suggested that this finding is in response to electrical fields across the corneal surface (Dua et al, 1993(Dua et al, , 1996. In contrast, in our model, both clockwise and counterclockwise whorls were observed, apparently randomly with respect to left and right eyes, but only in the very centre of the cornea.…”
Section: Discussioncontrasting
confidence: 60%
“…18 However, the whorls in the GFPU mouse cornea were both clockwise and counterclockwise, similar to those in the Lac-Z chimeric mice, 17 and therefore the electromagnetic theory does not seem applicable to these mice.…”
Section: Vortex Pattern Of Gfpmentioning
confidence: 95%
“…The presence of detectable donor cells in all test samples from the patient would suggest that extensive cell migration over the corneal surface is able to occur, as has been suggested by studies of models of corneal epithelial loss. 18 Further studies intend to clarify whether these findings do represent geniune survival of low levels of donor cells or merely a tantalising but erroneous picture.…”
Section: Comments On Preliminary Studies With Y-specific Probesmentioning
confidence: 99%